A didatização do gênero discursivo poema : uma análise enunciativo-discursiva bakhtiniana - Erdei, Leni Dias de Sousa (2014)
During our research, we reflected on schooling and didactization of the poem genre, inserted in the Poets of School Notebook of the Portuguese Language Olympics Program Escrevendo o Futuro (Writing the Future) (OLPEF), a public-private partnership between MEC and Fundação Itaú Social, under the technical coordination of São Paulo’s NGO CENPEC. The proposed material includes both the teaching of reading and textual production of the poem genre, for the Brazilian public school students in the 5th and 6th years of elementary school, as well as teacher training based on the formalist view of language. The OLPEF continuously expands its field in daily school practices, though its quality is not evaluated institutionally, and, in the academies, it still occupies little space in the analyses. Our research originated from the consideration of one the findings of Padilha (2005), in her doctoral thesis - Os gêneros poéticos em livros didáticos de língua portuguesa do Ensino Fundamental: uma abordagem enunciativo-discursiva. In it, the author states that the different ways to approach the genre of poetic discourse in textbooks demonstrate the theoretical misunderstandings of these materials, in regards to what is to be the conception of literary genres and, more specifically, of poems discursive genres. Such endeavors are linked, still, to studies grounded in literary theory, permeated by formalist conceptions which privilege, especially, the aspects of compositional form. Our objective was to describe the ways in which discursive genre poem was taught in the 2nd edition of the Poets of School Notebook of the Portuguese Language Olympics Program Escrevendo o Futuro (Writing the Future) 2010 and suggest a reading and production of poem in the enunciative-discursive perspective, considering formal, socio-historical, discursive and ideological aspects, embedded in the verbal creation process. Our reflections and analyses were based mainly on enunciative-discursive theory of socio-historical approach of Bakhtin and the Circle and in the theory of teaching and learning of Vygotsky. The analysis of the didactic model revealed that the conception of language as communication and formal approach of the poem takes the teaching to a traditional direction in which identifying, memorizing and locating are priorities in the study of the poetic text. Added to this, the didactic sequence, developed by Genevan scholars, tend to treat the poem rigidly, without giving opening to the teacher for changing the planning. At the end of our investigation, we wish that students can take, early on, the word, in a democratic way, in the country in which they live, so the gaze of the teaching of the first language should be facing the reading and production of texts in different discursive genres and, furthermore, to the search for and understanding of dialogical relations in them.